Inclination towards entrepreneurship among university students: evidence from Malaysia - Mustapha, Mazlina; Selvaraju, Maitilee (School of Social Sciences, Universiti Sains Malaysia, 2012)
This paper aims to explore the factors that influence the students’ intention to be entrepreneurs at Malaysian universities. Among others, the influence of entrepreneurship education, the university’s role, family and peers, and demographic characteristics on the students’ inclination towards entrepreneurs are investigated. Self-administered questionnaires were distributed to Accounting students at three public universities in Klang Valley. About 180 questionnaires were completed and used for the purpose of this study. Regression analysis was employed to analyse the data. The results indicate that there is a moderate inclination towards entrepreneurship among the Accounting students. Entrepreneurship curriculum and course content, the role of university, perceived skills and ability, image of entrepreneurs, and peers and family significantly influence the students’ intention to be entrepreneurs. However, gender is not an important factor in influencing the students to choose entrepreneurship as their future career choice. The results appear to suggest that gender of a Malaysian student is not an important factor to determine whether he or she would venture into a business.